GaO (at) Mo2C MXene surface chemical adsorption type heterojunction composite material and preparation method and application thereof
The GaO@Mo2C MXene heterojunction composite material was prepared by a one-step hydrothermal reaction method, which solved the problems of complicated preparation steps and poor bonding stability of Mo2C MXene-based heterojunctions. It achieved stable chemical adsorption of GaO zero-dimensional particles and Mo2C MXene, improved the cycling stability and electron transport efficiency of the material, and made it suitable for catalysis and energy storage.
Patent Information
- Application Number
- CN202511748942.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-26
- Publication Date
- 2026-03-20
AI Technical Summary
Existing Mo2C MXene-based heterojunctions suffer from cumbersome preparation steps, poor stability of active component-substrate bonding, and easy agglomeration of 0D nanoparticles, leading to unstable material properties.
A one-step hydrothermal reaction method was adopted, in which Mo2Ga2C powder was etched with NH4Cl solution at 200-220℃, and Ga elements were simultaneously etched and oxidized to generate GaO zero-dimensional particles. At the same time, Mo2C MXene was exfoliated, and the GaO zero-dimensional particles were bonded to the surface of Mo2C MXene through chemical adsorption to form GaO@Mo2C MXene heterojunction composite material.
The preparation process is simplified, the bonding stability between GaO zero-dimensional particles and Mo2C MXene is improved, particle detachment is avoided, and the cycling stability and electron transport efficiency of the material are enhanced, making it suitable for catalysis and energy storage applications.
Smart Images

Figure CN121709614A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of materials, and particularly relates to a GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material and a preparation method and application thereof. BACKGROUND
[0002] As a new type of two-dimensional layered nanomaterial, MXene material has high specific surface area, excellent electrical conductivity and good chemical stability, and shows broad application prospects in the fields of catalysis, supercapacitors, sensors and the like. Mo2C MXene, as an important member of the MXene family, has become a popular substrate material for heterostructure construction due to its unique electronic structure and catalytic activity.
[0003] The performance of a heterojunction composite material is largely dependent on the combination mode and dispersibility of the active component and the substrate. Traditional Mo2C MXene-based heterojunctions are prepared by a multi-step method, i.e., Mo2C MXene is first prepared, and then the active component is loaded by physical mixing or sol-gel method. This method has problems such as complicated steps, uneven dispersion of the active component, weak binding force (mostly physical adsorption) between the active component and the substrate, and the like, which leads to poor stability of the heterojunction, and the active component is prone to falling off during the recycling process, thereby affecting the performance of the material.
[0004] In addition, zero-dimensional (0D) nanoparticles have excellent catalytic activity and optical performance due to the quantum size effect, but they are prone to agglomeration when existing alone, which limits their application. The construction of a heterojunction between 0D nanoparticles and 2D Mo2C MXene can inhibit the agglomeration of 0D particles by utilizing the layered structure of MXene, and at the same time, the electronic transmission efficiency of the heterojunction can be improved through interface interaction. However, the existing preparation methods are difficult to realize stable chemical adsorption combination of 0D particles and Mo2C MXene, and the preparation process is complicated and time-consuming.
[0005] Therefore, it is necessary to provide an improved technical solution to solve the above problems in the prior art. SUMMARY
[0006] The purpose of the present application is to provide a GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material and a preparation method and application thereof, so as to help solve or improve at least one of the problems of complicated preparation steps of Mo2C MXene-based heterojunctions, poor binding stability of the active component and the substrate, and easy agglomeration of 0D particles.
[0007] In order to achieve the above object, the present application provides the following technical scheme: a preparation method of GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material, characterized in that it comprises the following steps: (1) Mo2Ga2C powder is added into NH4Cl solution, and after being uniformly mixed, it is transferred to a reaction container; (2) hydrothermal reaction; the temperature of the hydrothermal reaction is 200-220 DEG C; (3) after the hydrothermal reaction is completed, solid-liquid separation, washing and drying are carried out, and the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material is obtained.
[0008] Preferably, in step (2), the time of the hydrothermal reaction is 24-48 h.
[0009] Preferably, the concentration of the NH4Cl solution is 0.5-1.5 mol / L.
[0010] Preferably, in step (1), the mass-volume ratio of Mo2Ga2C powder to NH4Cl solution is 15-25 g / L.
[0011] Preferably, in step (3), the mode of solid-liquid separation is centrifugation; the speed of centrifugation is 8000-10000 r / min, and the time of centrifugation is 10-15 min.
[0012] Preferably, in step (3), deionized water and anhydrous ethanol are used alternately for washing until the washing liquid is neutral.
[0013] Preferably, in step (3), the mode of drying is vacuum drying; the temperature of drying is 60-80 DEG C, and the time of drying is 12-24 h.
[0014] The present application also provides a GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material, which adopts the following technical scheme: a GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material is prepared by the method described above.
[0015] The present application also provides an electrode, which adopts the following technical scheme: an electrode, wherein the components of the electrode comprise the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material described above.
[0016] The present application also provides a battery, which adopts the following technical scheme: a battery, wherein the battery contains the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material described above or the electrode described above.
[0017] Beneficial effects: The GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material preparation method of the application takes Mo2Ga2C as raw material, uses the etching effect of NH4Cl solution under hydrothermal conditions to realize the etching and oxidation of Ga element in Mo2Ga2C to generate GaO zero-dimensional particles, and the peeling of Mo2C MXene at the same time, and finally combines GaO zero-dimensional particles on the surface of Mo2C MXene through chemical adsorption to form GaO(0D)@Mo2C MXene heterojunction composite material.
[0018] The GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material preparation method of the application is a one-step method for preparing GaO(0D)@Mo2C MXene surface chemical adsorption type heterojunction composite material, which can realize the synchronous preparation and stable chemical adsorption of GaO zero-dimensional particles and Mo2C MXene; the preparation method of the application significantly simplifies the preparation process, shortens the preparation period, reduces the production cost, and helps to improve the lithium storage performance of the heterojunction.
[0019] In the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material of the application, GaO zero-dimensional particles and Mo2C MXene are combined through chemical adsorption, which has stronger binding force than traditional physical adsorption, can effectively prevent the GaO particles from falling off during use, and helps to improve the cycle stability of the heterojunction composite material.
[0020] In the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material of the application, GaO zero-dimensional particles are uniformly dispersed without obvious agglomeration, which can fully play its quantum size effect; at the same time, the high conductivity of Mo2C MXene can promote the interface electron transmission, and the synergistic effect of the two makes the material have excellent performance in the fields of catalysis and energy storage. BRIEF DESCRIPTION OF DRAWINGS
[0021] The drawings accompanying the specification of this application serve to provide further understanding of the application, and the illustrative embodiments of the application and their descriptions serve to explain the application, and do not constitute improper limitations on the application. Among them: Figure 1 The XRD patterns of the products prepared in Examples 1-3 and Comparative Examples 1-2 and pure phase Mo2Ga2C; Figure 2 The SEM pattern of pure phase Mo2Ga2C, showing its original morphology and element composition (high Ga content); Figure 3 The SEM pattern of pure phase Mo2C MXene prepared in Comparative Example 2, showing its layered structure and a significant reduction in Ga content after etching; Figure 4The SEM image of the pure-phase Mo2C MXene / Mo2Ga2C prepared for Comparative Example 1 shows the layered structure and the greatly reduced Ga content after etching; Figure 5 The SEM image of the GaO(0D)@Mo2C MXene surface chemical adsorption type heterojunction composite material prepared for Example 1 shows the dispersion state of the GaO zero-dimensional particles on the surface of the Mo2C MXene; Figure 6 The selected area SEM image of the GaO(0D)@Mo2C MXene surface chemical adsorption type heterojunction composite material prepared for Example 1 further observes the microstructure details of the heterojunction; Figure 7 The selected area EDS image of the GaO(0D)@Mo2C MXene surface chemical adsorption type heterojunction composite material prepared for Example 1 can clearly show the element composition and content of the composite material; Figure 8 The specific capacity test result graph of the charge-discharge cycle of each type of anode (Example 1, Comparative Example 1, Comparative Example 2) for 10 times under different current densities; Figure 9 The specific capacity test result graph of the charge-discharge cycle of different anodes for 100 times under a current density of 0.1 A / g. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present application will be described in detail below. Obviously, the described embodiments are only a part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art belong to the scope of protection of the present application.
[0023] The present application will be described in detail below. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict.
[0024] The present application provides a preparation method of a GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material, aiming at at least one of the problems of complicated preparation steps of Mo2C MXene-based heterojunction, poor stability of active components and substrate combination, and easy agglomeration of 0D particles.
[0025] The preparation method of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material according to the embodiment of the application comprises the following steps: (1) Mo2Ga2C powder is added to an NH4Cl solution, and after being uniformly mixed, it is transferred to a reaction container (preferably, the reaction container can be a polytetrafluoroethylene-lined reaction kettle); (2) hydrothermal reaction; the temperature of the hydrothermal reaction is 200-220 DEG C (for example, 200 DEG C, 205 DEG C, 210 DEG C, 215 DEG C or 220 DEG C); (3) after the hydrothermal reaction is completed, solid-liquid separation, washing and drying are performed, and the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material is obtained.
[0026] In the preparation of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material according to the application, if the temperature of the hydrothermal reaction is too low or too high, the synergistic mechanism of "etching-oxidation-chemical adsorption" will be destroyed, which will have a significant adverse effect on the structure, GaO loading state and performance of the product: if the temperature of the hydrothermal reaction is too low, the etching effect of NH4Cl on Mo2Ga2C is insufficient, Mo2Ga2C is difficult to completely peel off into a Mo2C MXene layered structure, and the product is prone to form a mixed phase with unetched Mo2Ga2C raw materials; at the same time, the deintercalation rate of Ga elements is slow, the number of generated GaO zero-dimensional particles is small and the dispersion is uneven, part of the GaO will combine with the unetched raw materials instead of being effectively chemically adsorbed on the surface of the MXene, eventually leading to a blocked electronic transport path of the material, the quantum size effect of GaO cannot be fully played, and the specific capacity, rate performance and cycle stability are all significantly reduced; if the temperature of the hydrothermal reaction is too high (higher than 220 DEG C), the oxidation degradation of Mo2C MXene layers will be intensified, causing the collapse of the layered structure and the reduction of the specific surface area, losing the dispersion support effect on GaO particles; at the same time, the high temperature will accelerate the Ostwald ripening of GaO particles (small particles are dissolved and agglomerated into large particles), even cause the phase transition of GaO to generate inactive Ga2O3, and weaken the Ga-O-Mo coordination bond effect between GaO and Mo2C MXene, leading to the easy falling off of GaO particles, eventually reducing the electronic transport efficiency of the material and blocking the diffusion of lithium ions, and the specific capacity, cycle stability and rate performance are all deteriorated, which cannot meet the application requirements of catalysis, energy storage and the like.
[0027] The preparation method of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material of the application takes Mo2Ga2C as raw material, uses the etching effect of NH4Cl solution under hydrothermal conditions to simultaneously realize the etching of Ga element in Mo2Ga2C (Ga element is separated from the lattice), the oxidation of GaO zero-dimensional particles under the action of the hydrothermal environment, and the exfoliation of Mo2C MXene (Mo2C forms a layered MXene structure), and finally combines GaO zero-dimensional particles on the surface of Mo2C MXene through chemical adsorption to form GaO(0D)@Mo2C MXene heterojunction composite material.
[0028] The target heterojunction composite material can be prepared through one-step hydrothermal reaction, which helps to solve the problems of complicated preparation steps or poor combination stability of traditional heterojunctions.
[0029] In the preferred embodiment of the preparation method of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material of the application, the hydrothermal reaction time in step (2) is 24-48h (for example, 24h, 30h, 36h, 40h, 45h or 48h). In the preparation of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material of the application, if the hydrothermal reaction time is too short or too long, the dynamic balance of "Ga element deintercalation-oxidation nucleation-chemical adsorption" will be broken, which will adversely affect the product structure, GaO loading effect and final performance: if the hydrothermal reaction time is too short (for example, less than 24h), the etching reaction of NH4Cl on Mo2Ga2C is not fully carried out, Mo2Ga2C cannot be completely converted into Mo2C MXene, and the residual unetched raw material will be mixed with the generated GaO zero-dimensional particles, while the Ga element deintercalation and oxidation are not complete, the number of GaO particles is insufficient and cannot completely cover the surface active sites of Mo2C MXene, resulting in low GaO loading and uneven dispersion, which cannot form a stable chemical adsorption type heterojunction, and the disorderly distribution of particles will hinder electron transmission, so that the lithium storage specific capacity and rate performance of the material are not ideal, which is difficult to meet the basic requirements of catalysis or energy storage scenarios; if the hydrothermal reaction time is too long (for example, more than 48h), although the etching and oxidation reactions have reached equilibrium, excessive reaction will cause the Ostwald ripening phenomenon of GaO particles - small size GaO particles are dissolved and then deposited on the surface of large particles, resulting in agglomeration of GaO particles and loss of quantum size effect, and the long-term hydrothermal environment will slightly intensify the oxidation of Mo2C MXene layers, weaken the Ga-O-Mo coordination bond strength between Mo2C MXene and GaO particles, cause some GaO particles to fall off, finally reduce the specific surface area of the material and the interface electron transmission efficiency, and significantly deteriorate the cycle stability, which cannot adapt to the application scenarios with high requirements for performance consistency and long service life.
[0030] The GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material preparation method of the application can realize the regulation of the loading amount of GaO zero-dimensional particles by regulating the hydrothermal reaction conditions (temperature and time), and meets the needs of different application scenarios. The specific implementation mode is as follows: The GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material preparation method of the application realizes the regulation of the loading amount of GaO zero-dimensional particles by regulating the hydrothermal reaction temperature and time, and the core relies on the etching-oxidation synergistic effect of NH4Cl solution on Mo2Ga2C. The temperature determines the etching rate and oxidation efficiency, the reaction time determines the etching degree and adsorption accumulation, and both of them jointly affect the whole chain of "Ga element deintercalation-oxidation nucleation-chemical adsorption". In terms of temperature, the etching efficiency is improved in the medium-high temperature range of 200-220℃, and the loading amount is stable at 2.3-2.8at% (medium loading level, considering quantum size effect and electronic transmission efficiency, suitable for mainstream scenarios such as energy storage electrodes and catalysis). If the hydrothermal reaction temperature is too low, the effective loading amount will be reduced and the dispersion will be uneven. In terms of time, the loading amount is about 2.5at% when the reaction time is short (24h) (suitable for high-efficiency and medium-loading demand scenarios), the loading amount tends to be stable (2.3-2.8at%) and the particle dispersion is uniform when the reaction time is long (48h) (suitable for scenarios with high stability requirements such as long-cycle battery electrodes), and the particle agglomeration will reduce the effective loading sites when the reaction time exceeds 48h. By matching the temperature of 200-220℃ and the time of 24-48h, the loading amount of GaO zero-dimensional particles can be precisely adjusted in the range of 2.3-3.9at%. Among them, the specific capacity and cycle stability of the material are optimal at the medium loading level, the conductivity is better at the low loading level, and the parameter combination can be flexibly selected according to different application scenarios.
[0031] In the preferred embodiment of the preparation method of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material of the application, the concentration of the NH4Cl solution is 0.5-1.5mol / L (for example, 0.5mol / L, 0.8mol / L, 1mol / L, 1.2mol / L or 1.5mol / L). In the preparation of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material of the application, too high or too low concentration of the NH4Cl solution will destroy its etching-oxidation synergistic effect on Mo2Ga2C, and further adversely affect the product structure, GaO loading state and performance: if the concentration of NH4Cl is too low, the etching ions (Cl -) concentration, the etching intensity of Mo2Ga2C is weakened, which not only leads to the difficulty of Mo2Ga2C in fully peeling to form a Mo2C MXene layered structure, but also causes the residual unetched raw materials, and greatly reduces the de-intercalation rate of Ga element, resulting in a small amount of GaO zero-dimensional particles and uneven dispersion, and part of GaO even combines with the unetched raw materials instead of being effectively chemisorbed on the surface of the MXene, which finally causes the incomplete heterojunction structure and the blocked electronic transmission path, and the lithium storage specific capacity, rate performance and cycle stability of the material are significantly reduced, which cannot meet the basic performance requirements of catalysis or energy storage; if the concentration of NH4Cl is too high, the excessive Cl - will intensify the etching effect, leading to excessive etching of Mo2C MXene layers, collapse of the layered structure, edge damage, and reduction of the specific surface area, losing the dispersion and support effect on GaO particles, while high concentration of Cl - is easy to combine with Ga element to form soluble Ga-Cl compounds, resulting in a decrease in the amount of GaO zero-dimensional particles and a decrease in the effective loading amount, and the excessive Cl - is difficult to be completely removed by washing, which forms impurities on the surface of the material, hinders the interface electron transmission and lithium ion diffusion, and finally deteriorates the electrochemical performance of the material, accelerates the attenuation of the charge and discharge specific capacity, and deteriorates the cycle stability, which cannot adapt to high requirement application scenarios.
[0032] Preferably, the concentration of the NH4Cl solution is 1 mol / L.
[0033] In the preferred embodiment of the preparation method of the GaO@Mo2C MXene surface chemisorption type heterojunction composite material of the application, in step (1), the mass-volume ratio of Mo2Ga2C powder to NH4Cl solution is 15-25 g / L (for example, 15 g / L, 18 g / L, 20 g / L, 23 g / L or 25 g / L).
[0034] Preferably, in step (1), the mass-volume ratio of Mo2Ga2C powder to NH4Cl solution is 20 g / L.
[0035] In the preferred embodiment of the preparation method of the GaO@Mo2C MXene surface chemisorption type heterojunction composite material of the application, in step (3), the solid-liquid separation method is centrifugation; the centrifugation speed is 8000-10000 r / min (for example, 8000 r / min, 8500 r / min, 9000 r / min, 9500 r / min or 10000 r / min), and the centrifugation time is 10-15 min (for example, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min).
[0036] In the preferred embodiment of the preparation method of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material, in step (3), the deionized water and anhydrous ethanol are alternately used for washing until the washing liquid is neutral.
[0037] In the preferred embodiment of the preparation method of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material, in step (3), the drying temperature is less than or equal to 80 DEG C.
[0038] In the preferred embodiment of the preparation method of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material, in step (3), the drying method is vacuum drying, the drying temperature is 60-80 DEG C (for example, 60 DEG C, 65 DEG C, 70 DEG C, 75 DEG C or 80 DEG C), and the drying time is 12-24 h (for example, 12 h, 16 h, 20 h or 24 h).
[0039] The application further provides a GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material, which is prepared by the method described above.
[0040] In the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material, Ga is combined with the Mo2C MXene surface in the form of zero-dimensional GaO particles through chemical adsorption. The GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material can be widely applied in the fields of catalysis, energy storage, etc. (for example, the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material has excellent lithium storage performance).
[0041] Preferably, in the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material, the content of Ga is about 2.3 at%, the content of Mo is about 15.4 at%, the content of C is about 63.3 at%, and the content of O is about 19.0 at%.
[0042] The application further provides an electrode, and the components of the electrode include the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material.
[0043] The application further provides a battery, and the battery includes the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material or the electrode.
[0044] The GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material, the preparation method and the application thereof will be described in detail below through specific examples.
[0045] The sources of the main raw materials used in the following examples are as follows: Mo2Ga2C powder, manufacturer: Beijing Deke Daojin Technology Co., Ltd., model: "high-purity Mo2Ga2C MAX phase powder"; key parameters: purity ≥ 99% (metal impurity content ≤ 1%); element content: Mo: 51.59%, Ga: 27.9%, C: 20.5%, others: 0.01%; mesh size specification: 200-500 mesh; particle size distribution: 50-200 nm, crystal structure is hexagonal phase, no obvious agglomeration (verified by SEM, good particle dispersion); NH4Cl reagent, manufacturer: Shanghai Maikelin Biochemical Technology Co., Ltd., analytical pure (AR grade), purity ≥ 99.99% (anion impurity Cl - ≤0.01%), good water solubility, no deliquescence and caking phenomenon (dry in a 105°C oven for 2h before use to remove adsorbed water); preparation of 1 mol / L NH4Cl solution: ultrapure water (resistivity ≥ 18.2 MΩ·cm) is required to prepare 1 mol / L NH4Cl solution to avoid interference of impurity ions in water with the reaction, and the pH value of the solution should be detected by a pH meter after preparation (should be 5.5-6.5, weakly acidic); NH4F reagent, manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., analytical pure (AR grade), purity ≥ 99.99% (anion impurity F - ≤0.01%, cation impurities Na + , K + content ≤0.05%), white crystalline powder, no deliquescence (dry in a 80°C vacuum drying oven for 4h before use to remove crystal water and avoid concentration deviation); preparation of 1 mol / L NH4F solution: use ultrapure water (resistivity ≥ 18.2 MΩ·cm) to prepare, stir until completely dissolved, and use immediately after preparation (normal 1 mol / L NH4F solution pH should be 7.5-8.5, if pH <7, reprepare); Deionized water: laboratory grade ultrapure water prepared by a water machine, resistivity ≥ 18.2 MΩ·cm, total organic carbon (TOC) ≤ 5 ppb; Anhydrous ethanol: Shanxi Tongjie Chemical Reagent Co., Ltd., analytical pure (AR grade), purity ≥ 99.9%, water content ≤0.1%
[0046] Example 1 The preparation method of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material of the embodiment comprises the following steps: (1) Take 1 g of pure phase Mo2Ga2C powder. The XRD characteristic peaks of the powder are consistent with the "pure phase Mo2Ga2C" curve in Figure 1 , and it is ensured that it is a pure phase raw material; (2) The Mo2Ga2C powder taken is added to 40 mL of 1 mol / L NH4Cl solution, and stirred on a magnetic stirrer for 30 min to form a uniform suspension; (3) The suspension is transferred to a polytetrafluoroethylene-lined reaction kettle, and after the reaction kettle is sealed, it is placed in an oven, and the temperature of the oven is set to 220°C. The temperature is kept for 48 h; (4) After the reaction is completed, the oven is turned off, and the reaction kettle is naturally cooled to room temperature. The reaction product is taken out of the reaction kettle; (5) The reaction product is placed in a centrifuge tube, and a centrifuge is used at a speed of 10,000 r / min for 10 min. The precipitate at the bottom of the centrifuge tube is collected; (6) The precipitate is washed with deionized water and anhydrous ethanol alternately. After each washing, short-time centrifugal separation is performed, and the washing is repeated 3-5 times until the pH value of the washing liquid is 7, so as to ensure that the residual NH4Cl and impurities are removed; (7) The washed precipitate is placed in a vacuum drying oven, the drying temperature is set to 60°C, and the drying time is 24 h. After drying, the GaO(0D)@Mo2C MXene surface chemical adsorption type heterojunction composite material of the embodiment is obtained.
[0047] The GaO(0D)@Mo2C MXene surface chemical adsorption type heterojunction composite material of the embodiment is subjected to SEM and EDS tests. The product characteristics obtained by the tests are as follows: the content of Ga element is about 2.3 at%, the content of Mo element is about 15.4 at%, the content of C element is about 63.3 at%, and the content of O element is about 19.0 at%. The GaO zero-dimensional particles are uniformly dispersed and have no obvious agglomeration.
[0048] Example 2 The difference between the embodiment and example 1 is only that the hydrothermal reaction time is 24 h. The rest is the same as example 1.
[0049] The GaO(0D)@Mo2C MXene surface chemical adsorption type heterojunction composite material of the embodiment is subjected to SEM and EDS tests. The product characteristics obtained by the tests are as follows: the content of Ga element is about 2.5 at%, the content of Mo element is about 15.5 at%, the content of C element is about 63.2 at%, and the content of O element is about 18.8 at%. The GaO zero-dimensional particles have uniform particle size (5-8 nm) and no agglomeration.
[0050] Example 3 The difference between this example and Example 1 is only that the temperature of the hydrothermal reaction is 200°C, and the reaction time is 48h; the rest is consistent with Example 1.
[0051] The GaO(0D)@Mo2C MXene surface chemical adsorption type heterojunction composite material of this example was tested by SEM and EDS, and the product characteristics obtained by testing were: the content of Ga element was about 2.4at%, the content of Mo element was about 15.3at%, the content of C element was about 63.5at%, and the content of O element was about 18.8at%; the GaO particles were closely combined with the Mo2C MXene interface, and the layered structure was complete.
[0052] Example 4 The preparation method of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material of this example comprises the following steps: (1) 1g of pure phase Mo2Ga2C powder was weighed and added to 50mL of 1mol / L NH4Cl solution, and stirred on a magnetic stirrer for 30min to form a uniform suspension; (2) Hydrothermal reaction: the above suspension was transferred to a polytetrafluoroethylene lined reaction kettle, sealed and placed in an oven, the temperature was set to 210°C, and the reaction was carried out for 36h; (3) After the reaction was completed, the oven was turned off, and the reaction kettle was naturally cooled to room temperature, and the reaction product was taken out; (4) Solid-liquid separation: the reaction product was placed in a centrifuge tube, and a centrifuge was used at a speed of 9000r / min for 12min, and the precipitate at the bottom was collected; (5) Washing: deionized water and anhydrous ethanol were used to wash alternately for 3-5 times until the washing liquid pH=7; (6) Drying: the precipitate was placed in a vacuum drying oven and dried at 70°C for 18h to obtain the GaO(0D)@Mo2C MXene surface chemical adsorption type heterojunction composite material of this example.
[0053] The GaO(0D)@Mo2C MXene surface chemical adsorption type heterojunction composite material of this example was tested by SEM and EDS, and the product characteristics obtained by testing were: the content of Ga element was about 2.1at%, the content of Mo element was about 15.2at%, the content of C element was about 63.5at%, and the content of O element was about 19.2at%; the GaO zero-dimensional particles were uniformly dispersed without obvious agglomeration.
[0054] Example 5 The preparation method of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material of this example comprises the following steps: (1) 0.8 g of pure-phase Mo2Ga2C powder was weighed and added to 40 mL of 1 mol / L NH4Cl solution, with a powder-to-solution mass-to-volume ratio of 20 g / L; magnetic stirring was performed for 30 min to form a uniform suspension; (2) Hydrothermal reaction: the above suspension was transferred to a polytetrafluoroethylene-lined reaction kettle, the oven temperature was set to 200°C, and the reaction was performed for 24 h; (3) After the reaction was completed, the oven was turned off, the reaction kettle was allowed to cool naturally to room temperature, and the reaction product was removed from the reaction kettle; (4) Solid-liquid separation: the reaction product was placed in a centrifuge tube, and a centrifuge was used at a speed of 8000 r / min for 10 min to collect the precipitate at the bottom; (5) Washing: the product was washed 3-5 times alternately according to the method of Example 1 until the pH of the washing liquid was 7.
[0055] (6) Drying: the precipitate was placed in a vacuum drying oven and dried at 60°C for 12 h to obtain the GaO@Mo2C MXene surface chemisorbed heterojunction composite material of this example.
[0056] The GaO(0D)@Mo2C MXene surface chemisorbed heterojunction composite material of this example was subjected to SEM and EDS testing, and the product properties obtained by testing were as follows: the Ga element content was about 1.8 at%, the Mo element content was about 15.0 at%, the C element content was about 64.0 at%, and the O element content was about 19.2 at%; GaO and Mo2C MXene were combined by stable chemical adsorption.
[0057] Example 6 The GaO(0D)@Mo2C MXene surface chemisorbed heterojunction composite material of this example was prepared by the following method, which comprises the following steps: (1) 1.2 g of pure-phase Mo2Ga2C powder was weighed and added to 60 mL of 1 mol / L NH4Cl solution, with a powder-to-solution mass-to-volume ratio of 20 g / L; magnetic stirring was performed for 35 min to ensure that the high amount of powder was fully dispersed, and a uniform suspension was formed; (2) Hydrothermal reaction: the above suspension was transferred to a polytetrafluoroethylene-lined reaction kettle, the oven temperature was set to 220°C, and the reaction was performed for 24 h; (3) After the reaction was completed, the oven was turned off, the reaction kettle was allowed to cool naturally to room temperature, and the reaction product was removed from the reaction kettle; (4) Solid-liquid separation: the reaction product was placed in a centrifuge tube, and a centrifuge was used at a speed of 10000 r / min for 10 min to collect the precipitate at the bottom; (5) Washing: the product was washed 5 times alternately according to the method of Example 1 until the pH of the washing liquid was 7, and residual NH4Cl and impurities were removed; (6) drying: the precipitate was placed in a vacuum drying oven and dried at 80°C for 12h to obtain the GaO@Mo2C MXene surface chemisorbed type heterojunction composite material of the example.
[0058] The GaO(OD)@Mo2C MXene surface chemisorbed type heterojunction composite material of the example was tested by SEM and EDS, and the product properties obtained by the test were: the Ga element content was about 2.5at%, the Mo element content was about 15.6at%, the C element content was about 63.0at%, and the O element content was about 18.9at%; the GaO quantum size effect was significant.
[0059] Example 7 The preparation method of the GaO@Mo2C MXene surface chemisorbed type heterojunction composite material of the example includes the following steps: (1) 1g of pure phase Mo2Ga2C powder was weighed and added to 50mL of 1mol / L NH4Cl solution, and the mass / volume ratio of the powder to the solution was 20g / L; magnetic stirring for 45min ensured that the powder was fully dispersed at low temperature to form a uniform suspension; (2) hydrothermal reaction: the suspension was transferred to a polytetrafluoroethylene lined reaction kettle, the oven temperature was 200°C, and the reaction was carried out for 48h; (3) after the reaction was completed, the oven was turned off, the reaction kettle was naturally cooled to room temperature, and the reaction product was taken out by opening the reaction kettle; (4) solid-liquid separation: the reaction product was placed in a centrifuge tube and centrifuged at 8000r / min for 15min using a centrifuge to collect the precipitate at the bottom; (5) washing: the product was washed according to the method of example 1 for 4 times alternately until the pH of the washing liquid was 7; (6) drying: the precipitate was placed in a vacuum drying oven and dried at 60°C for 24h to obtain the GaO@Mo2C MXene surface chemisorbed type heterojunction composite material of the example.
[0060] The GaO(OD)@Mo2C MXene surface chemisorbed type heterojunction composite material of the example was tested by SEM and EDS, and the product properties obtained by the test were: the Ga element content was about 2.4at%, the Mo element content was about 15.3at%, the C element content was about 63.2at%, and the O element content was about 19.1at%; the layered structure was complete and the GaO particles did not fall off.
[0061] Example 8 The preparation method of the GaO@Mo2C MXene surface chemisorbed type heterojunction composite material of the example includes the following steps: (1) Take 1.5 g of pure phase Mo2Ga2C powder and add it to 75 mL of 1 mol / L NH4Cl solution, with a powder to solution mass volume ratio of 20 g / L; magnetically stir for 50 min to ensure that the high amount of powder is dispersed without agglomeration, forming a uniform suspension; (2) Hydrothermal reaction: transfer the above suspension to a polytetrafluoroethylene-lined reaction kettle, set the oven temperature to 215°C, and react for 30 h; (3) After the reaction is complete, turn off the oven and allow the reaction kettle to cool naturally to room temperature, then open the reaction kettle and remove the reaction product; (4) Solid-liquid separation: place the reaction product in a centrifuge tube and use a centrifuge to centrifuge at a speed of 9500 r / min for 13 min, and collect the precipitate at the bottom; (5) Washing: wash alternately 5 times according to the method of Example 1 until the pH of the washing liquid is 7; (6) Drying: place the washed precipitate in a vacuum drying oven at 75°C and dry for 20 h to obtain the GaO@Mo2C MXene surface chemisorbed type heterojunction composite material of this example.
[0062] The GaO(0D)@Mo2C MXene surface chemisorbed type heterojunction composite material of this example was subjected to SEM and EDS testing, and the product properties obtained by testing were: Ga element content of about 2.6 at%, Mo element content of about 15.5 at%, C element content of about 62.8 at%, and O element content of about 19.1 at%, which still maintained uniform dispersibility under large-scale preparation.
[0063] Comparative Example 1 The difference between this comparative example and Example 2 is only that the hydrothermal reaction temperature is 180°C and the hydrothermal reaction time is 24 h; the rest are the same as Example 1.
[0064] The product obtained in this comparative example was subjected to SEM and EDS testing, and the product properties obtained by testing were: Ga element content of 3.9 at%, Mo element content of 14.7 at%, C element content of 67.6 at%, and O element content of 13.8 at%.
[0065] Comparative Example 2 The difference between this comparative example and Comparative Example 1 is only that an equal concentration of NH4F solution is used instead of NH4Cl solution; the rest are the same as Comparative Example 1.
[0066] The product obtained in this comparative example was subjected to SEM and EDS testing, and the product properties obtained by testing were: Ga element content of about 0.1 at%, Mo element content of about 16.1 at%, C element content of about 66.5 at%, and O element content of about 17.3 at%. This may be because F - reacts with Ga 3+The Ga element is lost in large quantities (only 0.1 at%) and no effective chemical adsorption heterojunction is formed.
[0067] Comparative Example 3 The difference between this comparative example and Example 1 is only that the hydrothermal reaction time is 72 h, and the rest is consistent with Example 1.
[0068] The product obtained in this comparative example was tested by SEM and EDS, and the product properties obtained by testing were: the effective Ga element loading was reduced to 1.1 at%; this may be because excessive hydrothermal treatment led to oxidation and degradation of Mo2C MXene sheets, and the layered structure collapsed; GaO particles agglomerated, and part of them were converted into inactive Ga2O3 impurities.
[0069] Comparative Example 4 The difference between this comparative example and Example 1 is only that in step (1), the amount of Mo2Ga2C powder is 2 g, and the amount of NH4Cl solution is 50 mL (mass / volume ratio is 40 g / L), and the rest is consistent with Example 1.
[0070] In this comparative example, the high concentration of powder leads to uneven dispersion, and a large number of agglomerates are formed during the hydrothermal process, with a residual rate of un-etched Mo2Ga2C raw materials reaching 28%; the Mo2C MXene sheets are not completely exfoliated; The product obtained in this comparative example was tested by SEM and EDS, and the Ga element content obtained by testing was increased to 3.5 at% (but most of it was unreacted raw material residue, and the effective adsorption amount was only 1.3 at%)
[0071] Comparative Example 5 The difference between this comparative example and Example 1 is only that step (6) of alternating washing with deionized water and anhydrous ethanol is omitted, and the product is directly dried after centrifugation, and the rest is consistent with Example 1.
[0072] The product obtained in this comparative example was tested by SEM and EDS, and the results of the test showed that: a large amount of NH4Cl impurities remained on the surface of the precipitate (the Cl element content detected by EDS was 8.2 at%), and hard agglomerates were formed after drying, GaO particles were wrapped in impurities, and could not form effective chemical adsorption with Mo2C MXene.
[0073] Comparative Example 6 The difference between this comparative example and Example 1 is only that the vacuum drying temperature is 90°C, and the rest is consistent with Example 1.
[0074] The SEM and EDS tests on the product obtained in the present comparative example show that: the dehydration condensation of the hydroxyl (-OH) on the surface of Mo2C MXene occurs due to the excessively high drying temperature, the irreversible agglomeration of the layers occurs, the GaO particles are wrapped by the agglomerated layers, and the exposed active sites are reduced.
[0075] Comparative Example 7 The present comparative example differs from Example 1 only in that: no hydrothermal reaction is performed, and the Mo2C MXene and GaO powders are physically mixed by mechanical grinding.
[0076] The preparation process of the present comparative example is as follows: (1) pure-phase Mo2C MXene (according to the method of Comparative Example 1, only omitting the steps related to the generation of GaO) and pure-phase GaO powder are respectively prepared; (2) according to the element ratio (Ga element content of about 2.3 at%) of Example 1, the two powders are weighed and put into a ball mill for grinding for 30 min, and then vacuum dried (60°C x 24 h) after being mixed uniformly.
[0077] The SEM and EDS tests on the product obtained in the present comparative example show that: the physical mixing cannot form chemical adsorption, the GaO powder is only attached to the surface of Mo2C MXene by van der Waals force, the interfacial bonding force is weak; after drying, obvious delamination and agglomeration occur, and the GaO particles are easy to fall off;
[0078] Comparative Example 8 The present comparative example differs from Example 1 only in that: the hydrothermal reaction temperature is 250°C, and the rest is the same as Example 1.
[0079] The SEM and EDS tests on the product obtained in the present comparative example show that: high temperature leads to the oxidation and decomposition of Mo2C MXene; the GaO particles excessively grow, the particle size increases to 80-100 nm, and the quantum size effect is completely lost; The effective loading amount of Ga element is only 0.9 at%, which may be because the excessively high temperature of the hydrothermal reaction can cause the oxidation and decomposition of the material and the abnormal growth of the particles, and completely destroy the heterojunction performance.
[0080] Experimental Example 1. XRD test: The XRD patterns of the products prepared in Examples 1-3 and Comparative Examples 1-2 are shown in Figure 1 .
[0081] The successful preparation of the heterojunction of Examples 1-3 can be judged by the difference in the characteristic peaks in Figure 1 . Figure 1To prepare the XRD patterns of the products of Examples 1-3, Comparative Examples 1-2 and pure-phase Mo2Ga2C, which are used to visually verify the successful preparation of the target heterojunction composite material and to clearly distinguish the differences in the phase composition of the products. The "pure-phase Mo2Ga2C" curve in the pattern shows sharp and high-intensity characteristic diffraction peaks corresponding to its hexagonal crystal structure (consistent with the "crystal structure is hexagonal phase" in the raw material specification). These characteristic peaks are the key reference for judging whether the subsequent product is residual un-etched raw material, and their peak position and intensity can be used as a reference standard for phase comparison. The XRD curves of Examples 1-3 show consistent phase characteristics, clearly conveying the key information of "successful preparation of the target heterojunction", which is specifically manifested by the almost complete disappearance of the characteristic peaks of pure-phase Mo2Ga2C, indicating that the NH4Cl hydrothermal etching is sufficient and Mo2Ga2C has been completely stripped and converted into Mo2C MXene. At the same time, the typical broadened diffraction peaks of Mo2C MXene appear, proving the successful formation of the layered structure of Mo2C MXene. The absence of obvious sharp characteristic peaks of GaO is due to the uniform dispersion of GaO in the form of zero-dimensional nanoparticles on the surface of Mo2C MXene, and the low loading amount (2.3-2.8 at%), which is consistent with the rule that low-loading nanoparticles are difficult to show sharp peaks in XRD, indirectly proving the uniform dispersion of GaO particles.
[0082] The XRD curve of Comparative Example 1-2 is significantly different from that of the examples, directly reflecting the phase defects caused by the deviation of the preparation conditions. In Comparative Example 1 (hydrothermal at 180°C for 24h), part of the characteristic peaks of pure-phase Mo2Ga2C are still retained, and the characteristic peaks of Mo2C MXene are weak and not obviously broadened, indicating that the etching is not sufficient at low temperature, Mo2Ga2C is not completely stripped, and the product is a mixed phase of Mo2C MXene and Mo2Ga2C, which is consistent with the description of the product defect of "insufficient stripping of Mo2C MXene". In Comparative Example 2 (NH4F instead of NH4Cl), only the characteristic peaks of Mo2C MXene appear, without any Ga-related phase diffraction signals. Combined with the result of EDS detection that the Ga content is only 0.1 at%, it is proved that F - reacts with Ga 3+ to form soluble GaF3, resulting in the complete loss of Ga element and the absence of GaO, and the product is pure-phase Mo2C MXene without effective heterojunction.
[0083] In summary, Figure 1By the "existence, strength, and widening degree" of the phase characteristic peaks, the three core verifications are directly realized: Examples 1-3 have been completely converted into Mo2C MXene-based heterojunctions, there is no residual unetched raw material, and the target product is successfully prepared; Comparative Example 1 has residual raw materials due to insufficient low-temperature etching, and does not form a pure-phase heterojunction; Comparative Example 2 only obtains pure-phase Mo2C MXene due to improper selection of etchant, and does not construct GaO@Mo2C MXene heterojunctions.
[0084] 2. Elemental analysis and SEM testing: The SEM image of pure-phase Mo2Ga2C is shown in Figure 2 ; The elemental analysis of the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material of Example 1 showed that the Ga element content was 2.3 at%, the Mo element content was 15.4 at%, the C element content was 63.3 at%, and the O element content was 19.0 at%, and the Ga was in the form of zero-dimensional GaO particles combined on the surface of Mo2C MXene by chemical adsorption. The SEM image and EDS elemental analysis of the powder are shown in Figures 5-7 .
[0085] The SEM image and EDS elemental analysis of the product of Comparative Example 1 are shown in Figure 4 ; the elemental analysis results of the product of Comparative Example 1 showed that the Ga element content in the product prepared was 3.9 at%, the Mo element content was 14.7 at%, the C element content was 67.6 at%, and the O element content was 13.8 at%. That is, the product prepared by Comparative Example 1 is a Mo2C MXene / Mo2Ga2C composite material.
[0086] The SEM image and EDS elemental analysis of the product of Comparative Example 2 are shown in Figure 3 ; the elemental analysis results of the product of Comparative Example 2 showed that the Ga element content in the product prepared was 0.1 at%, the Mo element content was 16.1 at%, the C element content was 66.5 at%, and the O element content was 17.3 at%. That is, the product prepared by Comparative Example 2 is pure-phase Mo2C MXene.
[0087] 3. Specific capacity test under different current densities: All electrochemical tests were performed by CR2016 coin cells assembled at room temperature. The samples prepared in the above examples or comparative examples, acetylene black and polyvinylidene fluoride (PVDF) binder were mixed uniformly in N-methyl-2-pyrrolidone (NMP) solution at a mass ratio of 8:1:1. The electrodes with a diameter of 12 mm were prepared, and the mass loading was controlled in the range of 1.0-1.2 mg / cm. The obtained suspension was coated on a copper foil and vacuum dried at 110°C for 12 h. Then the CR2016 coin cells were assembled in an argon-filled glove box (purity: H2O < 1 ppm, O2 < 1 ppm) with lithium metal sheets as the counter electrode. The electrolyte was a 1 mol / L lithium hexafluorophosphate (LiPF6) ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) mixed solution (volume ratio 1:1:1), and a polypropylene separator (Celgard 2400) was used as the separator between the lithium foil and the active material. The EQCM440 battery tester of China Xinxing workstation was used to perform charge-discharge tests of the composite material at different current densities (0.05-0.5 A / g) in the voltage range of 0.01-3.0 V (vs. Li + / Li), and the results are shown in Figure 8 .
[0088] The specific capacity (185.2 / 112.4 / 61.0 mAh / g) of the GaO(0D)@Mo2C MXene surface chemisorption type heterojunction composite material (Example 1) prepared by the application was higher than that of the pure phase Mo2C MXene material (Comparative Example 2) (110.3 / 46.7 / 10.1 mAh / g) and the Mo2C MXene / Mo2Ga2C material (Comparative Example 1) (81.2 / 19.6 / 8.5 mAh / g) at different current densities of 0.1 A / g, 0.2 A / g, 0.5 A / g, etc., which embodied good rate performance. This was because the quantum size effect of the GaO zero-dimensional particles and the high conductivity of the Mo2C MXene synergistically enhanced the electronic transmission efficiency and electrochemical performance of the material.
[0089] 4. Cycle stability test: The charge-discharge cycle test was performed at a current density of 0.1 A / g, and the results are shown in Figure 9The specific capacity of the GaO(0D)@Mo2C MXene surface chemical adsorption type heterojunction composite material prepared by the application (Example 1) is also higher than that of the pure phase Mo2C MXene material (Comparative Example 2) and the Mo2C MXene / Mo2Ga2C material (Comparative Example 1) after 100 cycles, indicating that the composite material prepared by the application has more excellent cycle stability, which is due to the stable chemical adsorption combination between the GaO zero-dimensional particles and the Mo2C MXene, effectively avoiding the falling off of the GaO particles.
[0090] The electrochemical performance of the remaining examples and comparative examples is also tested, and the test results are shown in Table 1: Table 1
[0091] In summary, the preparation method provided by the application can successfully prepare the GaO(0D)@Mo2C MXene surface chemical adsorption type heterojunction composite material, which has excellent cycle stability and electrochemical performance, and can meet the application requirements in the fields of catalysis, energy storage and the like.
[0092] The above only describes the preferred embodiments of the application and is not used to limit the application. For those skilled in the art, the application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. within the spirit and principle of the application shall be included in the protection scope of the application.
Claims
1. A method for preparing a GaO@Mo2C MXene surface chemisorption type heterojunction composite material, characterized in that, Includes the following steps: (1) Add Mo2Ga2C powder to NH4Cl solution, mix well and then transfer to reaction vessel; (2) Hydrothermal reaction; the temperature of the hydrothermal reaction is 200-220℃; (3) After the hydrothermal reaction is completed, solid-liquid separation, washing and drying are performed to obtain the GaO@Mo2C MXene surface chemical adsorption type heterojunction composite material.
2. The preparation method of the GaO@Mo2C MXene surface chemisorption heterojunction composite material as described in claim 1, characterized in that, In step (2), the hydrothermal reaction takes 24-48 hours.
3. The preparation method of the GaO@Mo2C MXene surface chemisorption heterojunction composite material as described in claim 1, characterized in that, The concentration of the NH4Cl solution is 0.5-1.5 mol / L.
4. The preparation method of the GaO@Mo2C MXene surface chemisorption heterojunction composite material as described in claim 1, characterized in that, In step (1), the mass-to-volume ratio of Mo2Ga2C powder to NH4Cl solution is 15-25 g / L.
5. The method for preparing the GaO@Mo2C MXene surface chemisorption heterojunction composite material as described in claim 1, characterized in that, In step (3), the solid-liquid separation method is centrifugation; The centrifuge speed is 8000-10000 r / min, and the centrifugation time is 10-15 min.
6. The method for preparing the GaO@Mo2C MXene surface chemisorption heterojunction composite material as described in claim 1, characterized in that, In step (3), deionized water and anhydrous ethanol are used alternately for washing until the washing solution is neutral.
7. The preparation method of the GaO@Mo2C MXene surface chemisorption type heterojunction composite material as described in claim 1, characterized in that, In step (3), the drying method is vacuum drying; The drying temperature is 60-80℃, and the drying time is 12-24 hours.
8. A GaO@Mo2C MXene surface chemisorption type heterojunction composite material, characterized in that, The GaO@Mo2CMXene surface chemisorption heterojunction composite material is prepared by the method described in any one of claims 1-7.
9. An electrode, characterized in that, The electrode comprises the GaO@Mo2C MXene surface chemisorption heterojunction composite material as described in claim 8.
10. A battery, characterized in that, The battery contains the GaO@Mo2C MXene surface chemisorption heterojunction composite material as described in claim 8 or the electrode as described in claim 9.